Effect of Revulsive Compress on Pain and Range of Motion in Periarthritis of the Shoulder: A Study Protocol for a Quasi-Experimental Study - K, Jeyashree; S, Sadhana; M, Pandiaraja (Indian Journal of Integrative Medicine, 2025)
Periarthritis shoulder is an inflammatory painful musculoskeletal condition of the shoulder characterised by pain, stiffness and significant restriction of both active and passive range of motion particularly external rotation, abduction and flexion. Its prevalence is 2% to 5% in the general population. Its incidence is up to 20% in people with diabetes. Revulsive compress is a treatment modality which involves alternate application of hot (98-104°F) / (36-40°C) immediately followed by cold (55-65°F)/ (12-18°C). Revulsive compress seems to be effective in reducing pain and improving range of motion in periarthritis shoulder. Hence, we have designed this study to evaluate the effect of revulsive compress on pain and range of motion in periarthritis shoulder. Quasi experimental study design have been adopted. A total of 40 subjects between 40 and 65 years will be recruited. Subjects will be given revulsive compress for a period of 15 days. Baseline and post intervention assessments will be done for all subjects. Outcome variables are VAS Scale, SPADI and assessment of range of motion with goniometer. Data will be analysed using the Statistical Package for Social Sciences, Version 16. In this study, we will consider the p (probability) value of 0.05 to be statistically significant. If this study provides significant changes, then revulsive compress may be used as an adjuvant therapy in the management of periarthritis shoulder. Ethical clearance was obtained (IEC-IIYNMS/Approval/037/2023) and registered in a clinical trial (CTRI/2024/06/069038).